Legal Status of Overseas Marriage Registration in the Perspective of Indonesian Marriage Law - Romli, Muhammad; Luth, Thohir; Sulistyarini, Rachmi; Hamidah, Siti (Technium Social Sciences Journal, 2020)
This study aims to analyze the legal status of overseas marriage registration from the perspective of Indonesian marriage law. Law Number 16 of 2019, amendments to Law Number 1 of 1974 concerning Marriage, states that marriages conducted by Indonesian citizens outside Indonesia are legal if carried out according to law. which applies in the country where the marriage is taking place and for Indonesian citizens does not violate the provisions of the Marriage Law. Furthermore, within 1 (one) year after the husband and wife return to the territory of Indonesia, proof of their marriage must be registered at the marriage registration office where they live. There is still a problematic status of the registration law, whether it makes the validity of the marriage or is it only limited to the administrative order. This research uses a conceptual approach, a statutory approach, a historical approach and a philosophical approach. Legal materials used in this study consist of primary legal materials, secondary legal materials and tertiary legal materials which are normative in nature by searching, collecting and studying literature and documents, both conventionally and via the internet. The results of this study are the legal status of marriage registration abroad in the perspective of Indonesian marriage law, precisely in Article 56 of Law no. 16 of 2019 amendments to Law no. 1 of 1974 concerning Marriage, it can be concluded in general that the legal status of overseas marriage registration still does not provide legal certainty regarding the validity of marriage except for the extent of an administrative order. And there are three legal principles in Article 56 of the Marriage Law, namely: the lex patriae principle, the lex loci celebration principle and the principle of public order.